Implications of the codominance model for Hardy-Weinberg testing in genetic association studies - Wellek, Stefan; Müller-Nurasyid, Martina; Strauch, Konstantin (Human heredity, 2024)
Introduction: The standard way of using tests for compatibility of genetic markers with the Hardy-Weinberg equilibrium (HWE) assumption as a means of quality control in genetic association studies (GAS) is to carry out this step of preliminary data analysis with the sample of non-diseased individuals only. We show that this strategy has no rational basis whenever the genotype-phenotype relation for a marker under consideration satisfies the assumption of codominance. Methods: The justification of this statement is obtained through rigorous analytical arguments. Results: The key result of the paper is that there holds the following proposition: under the codominance model, the genotype distribution of a diallelic marker is in HWE among the controls if and only if the same is true for the cases. Conclusion: The major practical consequence of that theoretical result is that under the codominance model, testing for HWE should be done both for cases and controls aiming to establish the combined (intersection) hypothesis of compatibility of both underlying genotype distributions with the HWE assumption. A particularly useful procedure serving this purpose is obtained through applying the confidence-interval inclusion rule derived by Wellek, Goddard, and Ziegler (Biom J. 2010; 52:253-270) to both samples separately and combining these two tests by means of the intersection-union principle.
Artikel online veröffentlicht: 2. März 2024
Gesehen am 24.03.2025